ІНСТИТУЦІЙНЕ СПРИЯННЯ МОЖЛИВОСТІ ФАХОВОЇ ЗАЛУЧЕНОСТІ МОЛОДИХ УКРАЇНЦІВ В УМОВАХ ВІЙНИ - Siry, Evgeny; Sira, Oksana; Zaslavska, Lyudmyla (Zhytomyr Ivan Franko State University, 2025)
The article highlights key aspects of state support mechanisms for economic inclusion in the context of the youth segment and internally displaced persons. It also highlights the content of the problems of implementing state support in conditions of a protracted war. Within the framework of studying the main aspects of this issue, in accordance with its purpose, the tasks of the study included: identifying, clarifying and describing regulatory instruments in the development of the youth employment system; means and ways to increase the effectiveness of employment promotion in the youth environment, taking into account the challenges of the war. The material was prepared on the basis of expert interviews with relevant specialists in this area in terms of their substantive and practical views on various program fragments of state support for economic inclusion. The main “working” moments of individual problems and opportunities for program measures for state regulation of economic inclusion against the backdrop of the challenges of the war are shown. The above indicates that, despite the breadth and depth of the problem situation in the sphere of the functioning of the employment market, the state is making various efforts to resolve current strategic and tactical issues of optimizing the functioning and possible development of professional determination and economic inclusion of young people. It is shown by examples that the state is also making its own organizational adjustments to improve the situation on the labor market. In the implementation of relevant program areas to promote economic inclusion, special attention is paid to the issues of choosing means and mechanisms for regulating employment, tools for stabilizing and optimizing the labor market, professional retraining. career guidance systems, experience of state employment centers, the effectiveness of state programs that help internally displaced persons find jobs.